The variation of chemical characteristics of PM2.5 and PM10 and formation causes during two haze pollution events in urban Beijing, China. (April 2015) - Gao, Jiajia; Tian, Hezhong; Cheng, Ke; Lu, Long; Zheng, Mei; Wang, Shuxiao; Hao, Jiming; Wang, Kun; Hua, Shenbing; Zhu, Chuanyong; Wang, Yong
Abstract: Airborne particles in urban Beijing during haze days and normal days were collected and analyzed in the autumn and winter seasons to reveal the chemical characteristics variations of air pollution. The air quality in haze days was substantially worse than that in normal days. Both the relatively low wind speed and high relative humidity were in favor of the accumulation of pollution species and new formation of secondary PM2.5 in the atmosphere. Elevated concentrations of elements and water-soluble inorganic ions were found on haze days for both PM10 and PM2.5 . Particularly, the crustal element, such as Fe, in both PM10 and PM2.5 were substantially higher in autumn normal days and winter haze days than those in autumn haze days and winter normal days, indicating that the abundance of Fe in autumn haze days mainly be originated from crustal dust while in winter haze days it might be primarily emitted from anthropogenic sources (iron and steel smelting) instead of road dust. Secondary ion species (SO4 2−, NO3 −, NH4 + ) in particles were generated much more during haze episodes, and contributed a higher proportion in PM2.5 than in PM10 during the two sampling periods. Moreover, HYSPLIT model was used to explain the possible transport of airborne particles from distant sources. By comparing with south-type trajectory, west-type trajectory entrained larger amounts of primary crustal pollutants, while, south-type trajectory was comprised of a higher mass of anthropogenic pollution species. The results of back trajectory analysis indicated that the elevated concentration of aerosol and its chemical components during haze days might be caused by the integrated effects of accumulation under stagnant meteorological condition and the transport emissions of pollutants from anthropogenic sources surrounding Beijing city. Highlights: Stagnant weather factors and accumulated pollution species favor for haze formation. Elevated concentrations of elements and WSIIs are detected on haze days for both PM. Anthropogenic species are more inclined to accumulate and generate in fine particle. Aerosol is apt to more acidic on haze days due to more secondary species formation. Regional transport contributes the elevated content of anthropogenic elements in PM.